2016
DOI: 10.1177/1934578x1601100632
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of the Antibacterial Mechanism of Action of Juglone against Staphylococcus aureus

Abstract: Juglone is a plant-derived 1,4-naphthoquinone with confirmed antibacterial activity. However, the mechanism of action of juglone against Staphylococcus aureus remains unclear. Possible mechanisms were explored by a proteomic analysis of S. aureus proteins that are inhibited by juglone. Two-dimensional gel electrophoresis revealed that 21 protein spots were differentially expressed between juglone-treated and untreated cells of which 13 were identified. A bioinformatic analysis revealed that proteins participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Most of these proteins involved in translation and suggested that inhibition of translation might be the common pathway in the antifungal effect. Similar results had been obtained in a previous study [ 37 ], which reported that Pseudomonas aeruginosa treated with AgNPs–GE induces the expression of energy metabolism proteins. These results indicate that C .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most of these proteins involved in translation and suggested that inhibition of translation might be the common pathway in the antifungal effect. Similar results had been obtained in a previous study [ 37 ], which reported that Pseudomonas aeruginosa treated with AgNPs–GE induces the expression of energy metabolism proteins. These results indicate that C .…”
Section: Discussionsupporting
confidence: 91%
“…According to the soft guide, the spots were detected, matched and normalized based on the density of the gel and the percent volume. Calculations for the spots were performed at different statistical levels by the Kolmogorov-Smirnov test using ImageMaster 7.0 [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Juglone has been shown to possess antibacterial activities [57,58], and reportedly inhibits Gram-positive bacteria, Staphylococcus aureus [98]. Juglone exhibits a selective antimicrobial activity against different sources of Staphylococcus aureus strains.…”
Section: Antimicrobial Activity Of Juglonementioning
confidence: 99%
“…It is also likely that the mechanisms of antifungal and antibacterial actions of juglone involve redox cycling [14]. A bioinformatics analysis has shown that bacterial proteins that participate in DNA, RNA and protein synthesis as well as in the tricarboxylic acid cycle are inhibited by juglone [98]. It has also been reported that the antifungal and antibacterial activities of juglone nanoparticles are higher than those of free juglone, indicating that the nanoparticle formulation may be a promising way to enhance the beneficial effects of juglone [100,101].…”
Section: Antimicrobial Activity Of Juglonementioning
confidence: 99%
“…The antibacterial mechanism of anthratectone inhibits cell wall and nucleic acid synthesis (Malmir et al, 2017). The antibacterial mechanism through inhibiting electron transport, decoupling phosphorylation oxidative, production of reactive oxygen species (ROS) in aerobic condition, inhibiting DNA and RNA synthesis were reported for naphtotectone and juglone compounds (Babula et al, 2009;Wang et al, 2016). Nayeem and Karvekar (2011) said the antibacterial mechanism through inhibiting hydrolytic enzymes or another interaction that activates microbial adhesion were reported for rutin, quercetin, gallic acid, ellagic acid, and sitosterol compounds.…”
Section: Isolation Methods and Work Mechanism Of Teak Leaf Antibacterimentioning
confidence: 99%